O romance policial contemporâneo pelos caminhos da paródia: uma vertente metalinguística - Cordeiro, Fernando Henrique Crepaldi [UNESP] (2014)
This work intends to study the brazilian and portuguese contemporary crime novel, more specifically António Lobo Antunes' Tratado das paixões da alma (1990); Francisco José Viegas' Longe de Manaus (2005); Jô Soraes' O Xangô de Baker Street (1995) and Rubem Fonseca's Bufo & Spallanzani (1985), taking into account mainly the role played by the parody in these texts because when they subvert the traditional crime novel conventions, these texts promote its' gender boundaries enlargement. In contemporary narratives, unlike what used to happen in the noir and enigma novels, the investigation ceases to be seen as just a mean to reach the cases solution, being one of the narration fundamental elements. This change, according to this work perspective, is related to the destabilization of concepts such as truth, authority, objectivity, which were the crime texts foundations. When these notions are relativized, the investigation starts to be seen in the crime novels as a process of clue and vestige readings, being detected in the more recent narratives (from the 80s) an important structural displacement in relation to the traditional crime novel: the emphasis in the construction process of the detective narrative as well as of the novel as a whole. In other words, there is a deployment of the investigation notion that expands and contaminates the whole work, for, beyond the detective and the reader investigation, it puts us face a novel that investigates its own limits as well as its' gender's, in a dialogue that, for the one hand, report to the crime novel tradition and, for the other hand, reveal its own construction